Comparison of macular pigment and serum lutein concentration changes between free lutein and lutein esters supplements in Japanese subjects - Yoshizako, Hiroko; Hara, Katunori; Takai, Yasuyuki; Kaidzu, Sachiko; Obana, Akira; Ohira, Akihiro (Acta Ophthalmologica, 2016)
Purpose To compare changes in macular pigment optical density (MPOD) and serum lutein concentration between free lutein and lutein esters supplements in healthy Japanese individuals. Methods Twenty healthy subjects (age range, 22–47 years) were recruited into this prospective, randomized, doubled‐blind comparative study. Individuals were evenly divided into two groups: free lutein group, supplementation with 10 mg of free lutein; or lutein esters group, supplementation with 20 mg of lutein esters equivalent to 10 mg of free lutein. Each participant took either type of oral lutein daily for 3 months. The serum lutein concentrations and MPOD levels were measured at baseline and 3 and 6 months after the start of supplementation. Results There were no significant differences in the serum lutein concentrations and MPOD levels at baseline between the groups. The increased serum lutein concentration and MPOD levels at 3 months were respectively, 89% and 38% in the free lutein group and 97% and 17% in the lutein esters group. The serum lutein concentrations in both groups and MPOD levels in the free lutein group increased significantly (p < 0.05) from baseline. No significant differences in serum lutein concentrations and MPOD levels were seen between the groups. Three months after supplementation ended, the serum lutein concentration decreased; the MPOD remained elevated in both groups. Conclusions The serum lutein concentrations and MPOD levels increased significantly with either free lutein or lutein esters, and no significant differences were found between the two. Both were considered useful as lutein supplements.